Sorafenib Chemosensitization by Caryophyllane Sesquiterpenes in Liver, Biliary, and Pancreatic Cancer Cells: The Role of STAT3/ABC Transporter Axis - Silvia Di Giacomo; Marco Gullì; Roberta Facchinetti; Marco Minacori; Romina Mancinelli; Ester Percaccio; Caterina Scuderi; Margherita Eufemi; Antonella Di Sotto (MDPI AG, 2022)
A combination of anticancer drugs and chemosensitizing agents has been approached as a promising strategy to potentiate chemotherapy and reduce toxicity in aggressive and chemoresistant cancers, like hepatocellular carcinoma (HCC), cholangiocarcinoma (CCA), and pancreatic ductal adenocarcinoma (PDAC). In the present study, the ability of caryophyllane sesquiterpenes to potentiate sorafenib efficacy was studied in HCC, CCA, and PDAC cell models, focusing on the modulation of STAT3 signaling and ABC transporters; tolerability studies in normal cells were also performed. Results showed that the combination of sorafenib and caryophyllane sesquiterpenes synergized the anticancer drug, especially in pancreatic Bx-PC3 adenocarcinoma cells; a similar trend, although with lower efficacy, was found for the standard ABC transporter inhibitors. Synergistic effects were associated with a modulation of MDR1 (or Pgp) and MRP transporters, both at gene and protein level; moreover, activation of STAT3 cascade and cell migration appeared significantly affected, suggesting that the STAT3/ABC-transporters axis finely regulated efficacy and chemoresistance to sorafenib, thus appearing as a suitable target to overcome drawbacks of sorafenib-based chemotherapy in hepato-biliary-pancreatic cancers. Present findings strengthen the interest in caryophyllane sesquiterpenes as chemosensitizing and chemopreventive agents and contribute to clarifying drug resistance mechanisms in HCC, CCA, and PDAC cancers and to developing possible novel therapeutic strategies.